Variable Capacity for Acute and Chronic Thermal Compensation of Physiological Rates Contributes to Inter-Individual Differences in Growth Rate in Mussels (Mytilus galloprovincialis) - Prieto, Daniel; Arranz, Kristina; Urrutxurtu, Iñaki; Navarro, Enrique; Urrutia, Miren Bego; Ibarrola, Irrintzi (Frontiers in Marine Science, 2020)
The aim of this study was to ascertain if the capacity for acute and chronic compensation of thermal effects on physiological rates represents a trait contributing to inter-individual growth rate differences in the mussel Mytilus galloprovincialis. Juvenile mussels (10-11 mm shell length) were collected, transported to the laboratory, and divided into two groups: one group was maintained at 20ºC (warm treatment), and the other at 10ºC (cold treatment). The mussels were reared at these two temperatures (continuously fed), until clear size differences allowed us to select fast- (F) and slow (S)-growing individuals from both groups (F20/S20 at 20ºC and F10/S10 at 10ºC). Selected F and S mussels were then exposed to three experimental temperatures (10, 15, and 20ºC), and the time-course of their response, in terms of clearance rate (CR: L/h) and routine oxygen consumption (VO2: mLO2/h), was monitored. The overall growth rate of mussels in the warm treatment group was significantly higher than in the cold treatment group. For both treatments, significant differences were found in key physiological parameters between F and S mussels: F mussels had a higher CR and a larger gill surface area than their S counterparts. Although no significant differences in the thermal sensitivity of the clearance or metabolic rates were observed between F20 and S20 mussels reared at 20ºC, when exposed to acute temperature changes, experiments with mussels reared at 10ºC revealed a different outcome: in response to acute warming (from 10ºC to 15 and 20ºC), F10 were capable of compensating for the thermal effect on CR and VO2; however, no such compensatory response was observed in S10. We conclude that two significant factors contribute to endogenous differences in the growth rate of mussels: (i) the capacity to exhibit intense filtering activity, which appears to be functionally correlated with the gill surface area and ii) the capacity to compensate for the effects of temperature on filtration and metabolic rate. The second trait does not appear to make a significant contribution to the inter-individual size-differentiation observed in mussels maintained in warm environments, but explains a significant proportion of inter-individual growth rate differences in cold environments.